Performance Of Employees Procurement Of Goods And Services In The Riau Islands Province Through Job Satisfaction With Transformational Leadership As Moderating - Azwandi; Wibisono; Nurhatisyah; Bambang Satriawan; Nolla Puspita Dewi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The aim of this research is to analyze the direct influence between task complexity, competence, work culture and locus of control on the performance of goods and services procurement employees and to analyze the indirect influence between task complexity, competence, work culture and locus of control on the work of goods and services procurement employees. services which are moderated by the transformational leadership variable. The number of samples is the same as the population or by census or saturated sample method, as many as 163 employees managing the procurement of goods and services for the Riau Islands Province (PPK and Election Working Group). The data analysis method was carried out using descriptive statistics and data analysis using SEM and data processing using the smart PLS program. The R Square value of the combined or simultaneous influence of X1, X2, X3, and X4 on Y is 0.907 with an adjusted R Square value of 0.903. This can be explained that all exogenous constructs (X1, X2, X3, and X4) simultaneously influence Z by 90.30%. These findings prove that task complexity, competence, work culture and locus of control have a significant determination of the performance of procurement of goods and services in the Riau Islands Province and have an R Square value of combined or simultaneous influence of X1, X2, X3, and X4 on Z of 0.769 with an adjusted R Square value of 0.763. This proves that task complexity, competence, work culture and locus of control have significant determinants of job satisfaction of 76.30%. And the R Square value of the moderating effect on the performance of goods and services procurement employees is 0.775 with an adjusted R Square value of 0.770, meaning that the transformational leadership variable has an influence on the performance of goods and services procurement employees by 77%. The novelty of this research is that to optimize the performance of procurement of goods and services in the Riau Islands Province, researchers added one indicator to the locus of control variable, namely the need for spiritual intelligence (ESQ) in addition to emotional intelligence.